Hope is the first dose : a treatment plan for recovering from trauma, tragedy, and other massive things - Warren, W. Lee, 1969- (WaterBrook, 2023)
"A neurosurgeon's powerful memoir of personal tragedy, grief, and recovery offers a roadmap to finding hope and even happiness when the worst happens, by placing trust in God"--